Effects of a myofilament calcium sensitizer on left ventricular systolic and diastolic function in rats with volume overload heart failure - Wilson, Kristin (Am J Physiol Heart Circ Physiol, 2014)
Aortocaval fistula (ACF)-induced volume overload (VO) heart failure (HF) results in progressive left ventricular (LV) dysfunction. Hemodynamic load reversal during pre-HF (4 wk post-ACF; REV) results in rapid structural but delayed functional recovery. This study investigated myocyte and myofilament function in ACF and REV and tested the hypothesis that a myofilament Ca(2+) sensitizer would improve VO-induced myofilament dysfunction in ACF and REV. Following the initial sham or ACF surgery in male Sprague-Dawley rats (200–240 g) at week 0, REV surgery and experiments were performed at weeks 4 and 8, respectively. In ACF, decreased LV function is accompanied by impaired sarcomeric shortening and force generation and decreased Ca(2+) sensitivity, whereas, in REV, impaired LV function is accompanied by decreased Ca(2+) sensitivity. Intravenous levosimendan (Levo) elicited the best inotropic and lusitropic responses and was selected for chronic oral studies. Subsets of ACF and REV rats were given vehicle (water) or Levo (1 mg/kg) in drinking water from weeks 4–8. Levo improved systolic (% fractional shortening, end-systolic elastance, and preload-recruitable stroke work) and diastolic (τ, dP/dt(min)) function in ACF and REV. Levo improved Ca(2+) sensitivity without altering the amplitude and kinetics of the intracellular Ca(2+) transient. In ACF-Levo, increased cMyBP-C Ser-273 and Ser-302 and cardiac troponin I Ser-23/24 phosphorylation correlated with improved diastolic relaxation, whereas, in REV-Levo, increased cMyBP-C Ser-273 phosphorylation and increased α-to-β-myosin heavy chain correlated with improved diastolic relaxation. We concluded that Levo improves LV function, and myofilament composition and regulatory protein phosphorylation likely play a key role in improving function.